SINGLE SUBJECT RESEARCH : PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN E-MODUL TERHADAP KECERDASAN LOGIS MATEMATIS - Muqtafia, Khoirina; Wanabuliandari, Savitri; Sumaji (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2025)
Children with intellectual disabilities are special needs children with below-average intellectual mental retardation. This condition causes children with intellectual disabilities to face academic difficulties, particularly in mathematics, leading to low logical-mathematical intelligence. The aim of this study is to determine the development of students' logical-mathematical intelligence in mathematics learning on the topic of plane figures using a problem-based learning model assisted by an e-module. The method used in this study is single subject research with an A-B design consisting of two conditions: A as the baseline condition and B as the intervention condition. Data from both conditions were analyzed using within-condition analysis and between-condition analysis. The results of this study show an overlap percentage of 0%, indicating that the intervention has an increasingly positive effect on students' logical-mathematical intelligence.